Exogenous pancreatic kininogenase protects against renal fibrosis in rat model of unilateral ureteral obstruction - Jin Ji-zhe; Li Hui-ying; Jin Jian; Piao Shang-guo; Shen Xiong-hu; Wu Yan-ling; Xu Jia-chong; Zhang Long-ye; Jiang Yu-ji; Zheng Hai-lan; Jin Ying-shun; Cui Sheng; et al. (Acta Pharmacologica Sinica; Vol 41, No 12 (December 2020): Acta Pharmacologica Sinica, 2020)
Tissue kallikrein has protective function against various types of injury. In this study, we investigated whether exogenous pancreatic kininogenase (PK) conferred renoprotection in a rat model of unilateral ureteral obstruction (UUO) and H2O2-treated HK-2 cells in vitro. SD rats were subjected to UUO surgery, then PK (7.2 U/g per day, ip) was administered for 7 or 14 days. After the treatment, rats were euthanized; the obstructed kidneys were harvested for further examination. We found that PK administration significantly attenuated interstitial inflammation and fibrosis, and downregulated the expression of proinflammatory (MCP-1, TLR-2, and OPN) and profibrotic (TGF-β1 and CTGF) cytokines in obstructed kidney. UUO-induced oxidative stress, closely associated with excessive apoptotic cell death and autophagy via PI3K/AKT/FoxO1a signaling, which were abolished by PK administration. We further showed that PK administration increased the expression of bradykinin receptors 1 and 2 (B1R and B2R) mRNA and the production of NO and cAMP in kidney tissues. Coadministration with either B1R antagonist (des-Arg9-[Leu8]-bradykinin) or B2R antagonist (icatibant) abrogated the renoprotective effects of PK, and reduced the levels of NO and cAMP in obstructed kidney. In H2O2-treated HK-2 cells, addition of PK (6 pg/mL) significantly decreased ROS production, regulated the expression of oxidant and antioxidant enzymes, suppressed the expression of TGF-β1 and MCP-1, and inhibited cell apoptosis. Our data demonstrate that PK treatment protects against the progression of renal fibrosis in obstructed kidneys.